Groups in context : leadership the participation in small groups - Wilson, Gerald L., 1943- (Boston : McGraw-Hill College, 1999)
This book is divided into four parts: Approaching communication in group contexts; Preparing for group meeting; Participating in group meeting; Analyzing small group decisions making.
Keywords: Leadership; Small groups; Leadership; Group decision making; Small groups